Muscle density analysis in COVID-19 - Gundogan Bozdag , Pinar; Baykara, Murat; Pihtili Tas, Nevsun (Annals of Medical Research, 2022)
Aim: Coronavirus disease 2019 (COVID-19), declared epidemic by the World Health Organization, continues to spread globally and patients may not have specific symptoms of musculoskeletal involvement. Materials and Methods: Clinical data and images of 389 consecutive patients who presented to the pandemic outpatient clinic with a pre-diagnosis of COVID-19 and had musculoskeletal complaints and 203 consecutive control patients who underwent thoracic computed tomography (CT) examination for another reason and were evaluated as normal were examined. Bilateral sternocleidomastoid and trapezius muscle CT densities and blood creatine kinase (CK) levels of all participants were obtained. Results: In COVID-19 patients, a significant decrease in sternocleidomastoid muscle density compared to radiological grade, on the contrary, a significant increase in the density values of the trapezius muscle was detected. In terms of CK values, there was a significant increase in values such as trapezius density. Although the cause or effect is controversial, respiratory muscles associated with forced breathing were affected and muscle damage was found to occur. Conclusion: This study demonstrates the need for multicenter studies with detailed neurological and electrophysiological tests and pathological correlations in a sufficient number of patients.